You are on page 1of 3

# Math198 Tutorial Sheet 1

The questions on this sheet are for discussion in the Math198 tutorials. They are not for submission,
but you are strongly encouraged to attempt as many of them as possible to prepare for Homework 1 on
MyMathLab.
1. State the domain and range for the following real valued functions. For (a) and (b) find also the
inverse functions.
(a) f (x) = x3 2
t+4
(b) g(t) =
2t 3
(c) h() = sin (1/)
Solution:
(a) The domain and range are the whole set of real numbers (i.e. no forbidden values). To
calculate the inverse, we write
x =

So f 1 (x) =

y3

y3 2
x+2

3
x + 2.

x + 2.

(b) The domain is the set of real numbers t 6= 3/2. To calculate the inverse,
y+4
2y 3
(2y 3)t = y + 4
t =

y(2t 1)
y
So g 1 =

3t+4
2t1 .

3t + 4
3t + 4
=
.
2t 1

## The range of g is therefore all real numbers g 6= 1/2.

(c) The domain is the set of real numbers 6= 0. The range is the set of real numbers 1 h 1.
2. Differentiate each of the following functions.
(a) y = 4x3 5x2 + 3x4
(b) f (x) = x3 cos(x)
(c) y =

x4
sin(x)

(d) f (x) = (1 + x1 )3
ln t
(e) f (t) =
1+t
(f) y = e2x cos(x)
1

Solution:
(a) We have
dy
= 12x2 10x 12x5 .
dx
(b) The product rule gives
f 0 (x) = x3 sin(x) + 3x2 cos(x).
(c) The quotient rule gives
4x3 sin(x) x4 cos(x)
dy
=
.
dx
sin2 (x)
(d) Expanding gives
f (x) = 1 + 3x1 + 3x2 + x3 .
Differentiating term by term gives
f 0 (x) = 3x2 6x3 3x4 .
Alternatively, and probably more simply, using the Chain Rule gives
f 0 (x) = 3x2 (1 + x1 )2 = 3x2 6x3 3x4 .
(e) The quotient rule gives
f 0 (t)

=
=

1+t
t

+ ln t
(1 + t)2
1 + t + t ln t
.
t(1 + t)2

## (f) The product rule gives

dy
= e2x sin(x) + 2e2x cos(x).
dx
3. By considering small values of x, deduce the value of
lim

x0

cos(x) 1
.
x

Hence or otherwise find the derivative of y = cos(x) from first principles. (Hint: the formula
cos( + ) = cos() cos() sin() sin()
will be useful.)
Solution: Call the function

cos(x) 1
.
x

g(x) =

g(0.1)

0.05

g(0.01)

0.005

g(105 )
g(1010 )
We deduce that
lim

x0

5 106
5 1011 .

cos(x) 1
= 0.
x
2

## Let f (x) = cos(x). Then, according to first principles, we have

f 0 (x)

=
=
=
=
=

f (x + h) f (x)
h
cos(x + h) cos(x)
lim
h0
h
cos(x) cos(h) sin(x) sin(h) cos(x)
lim
h0
h
cos(h) 1
sin(h)
cos(x) lim
sin(x) lim
h0
h0
h
h
sin(x),
lim

h0